Cyanobacteria from coastal lagoons in southern Brazil: non-heterocytous filamentous organisms - Martins, Mariéllen Dornelles [UNESP]; Branco, Luis Henrique Zanini [UNESP]; Werner, Vera Regina (Sociedade Botânica de São Paulo, 2012)
This study describes and illustrates non-heterocytous filamentous cyanobacteria found in lagoon systems on the coastal plains of Rio Grande do Sul State. Collections were carried out in different freshwater bodies along the eastern (Casamento Lake area) and western (Tapes City area) margins of the Patos Lagoon (UTM 461948-6595095 and 542910-6645535) using a plankton net (25 µm mesh) in pelagic and littoral zones as well as by squeezing submerged parts of aquatic macrophytes, during both the rainy and dry seasons, from May to December/2003. Twenty two species belonging to the families Phormidiaceae (eight taxa), Pseudanabaenaceae (seven taxa), Oscillatoriaceae (six taxa), and Spirulinaceae (one taxon) were identified. Among these species, five are reported for the first time from Rio Grande do Sul State: Leptolyngbya cebennensis, Microcoleus subtorulosus, Oscillatoria cf. anguina, O. curviceps and Phormidium formosum.
Keywords: Oscillatoriaceae; Phormidiaceae; Pseudanabaenaceae; Spirulinaceae; taxonomic survey